2014
DOI: 10.1002/2013wr013711
|View full text |Cite
|
Sign up to set email alerts
|

Mountain system monitoring at Senator Beck Basin, San Juan Mountains, Colorado: A new integrative data source to develop and evaluate models of snow and hydrologic processes

Abstract: A hydrologic modeling data set is presented for water years 2006 through 2012 from the Senator Beck Basin (SBB) study area. SBB is a high altitude, 291 ha catchment in southwest Colorado exhibiting a continental, radiation-driven, alpine snow climate. Elevations range from 3362 m at the SBB pour point to 4118 m. Two study plots provide hourly forcing data including precipitation, wind speed, air temperature and humidity, global solar radiation, downwelling thermal radiation, and pressure. Validation data inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
2

Year Published

2015
2015
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 20 publications
1
87
2
Order By: Relevance
“…While previous investigations supported this idea for shortwave and longwave forcings in physically based snow models (i.e., Lapo et al, 2015), the current study showed that biases are more important than random errors for all commonly required meteorological forcings (and not just irradiances). The model was more sensitive to biases and less sensitive to random errors due to the systematic nature of biases.…”
Section: Error Typescontrasting
confidence: 63%
See 3 more Smart Citations
“…While previous investigations supported this idea for shortwave and longwave forcings in physically based snow models (i.e., Lapo et al, 2015), the current study showed that biases are more important than random errors for all commonly required meteorological forcings (and not just irradiances). The model was more sensitive to biases and less sensitive to random errors due to the systematic nature of biases.…”
Section: Error Typescontrasting
confidence: 63%
“…However, these studies have typically been limited to (1) empirical/conceptual models (He et al, 2011a, b;Raleigh and Lundquist, 2012;Shamir and Georgakakos, 2006;Slater and Clark, 2006), (2) errors for a subset of forcings (e.g., precipitation or temperature only) (Burles and Boon, 2011;Dadic et al, 2013;Durand and Margulis, 2008;Lapo et al, 2015;Xia et al, 2005), (3) model sensitivity to choice of forcing parameterization (e.g., longwave) without considering uncertainty in parameterization inputs (e.g., temperature and humidity) (Guan et al, 2013), and (4) simple representations of forcing errors (e.g., Kavetski et al, 2006a, b). The last is evident in studies that only consider single types of forcing errors (e.g., bias) and single distributions (e.g., uniform) and examines errors separately (Burles and Boon, 2011;Koivusalo and Heikinheimo, 1999;Raleigh and Lundquist, 2012;Xia et al, 2005).…”
Section: S Raleigh Et Al: Physical Model Sensitivity To Forcing mentioning
confidence: 99%
See 2 more Smart Citations
“…The research data must be compiled in a consistent format, be serially complete (at least for the model forcing data), and include estimates of the uncertainty and spatial representativeness of individual observations [Abramowitz, 2012]. Many of the emerging data papers from research basins cover these issues to varying degrees [e.g., Reba et al, 2011;Landry et al, 2014], but there is much more work to be done to pull together research data from a wide range of watersheds.…”
Section: Process-based Model Evaluationmentioning
confidence: 99%